pH-driven continuous stem cell production with enhanced regenerative capacity from polyamide/chitosan surfaces - Chia-Hsiang Yen; Nai-Chen Cheng; Hao-Ying Hsieh; Ching-Wen Tsai; An-Li Lee; Chien-Yi Lu; Yin-Tzu Chen; Tai-Horng Young (Materials Today Bio, 2023)
Adipose-derived stem cells (ASCs) have raised significant interest for their potential therapeutic applications in regenerative medicine. However, ASCs usually suffer from decreased pluripotency and functional plasticity during in vitro expansion. Herein, this study sought to develop a continuous cell production system that can mass-produce ASCs with sustained regenerative capacity. The strategy was blending pH-responsive chitosan (CS) with polyamide-66 (PA) to generate combined surface properties with controllable cell growth/detachment ability to achieve a repeated cell production process. From the collected data, all the polymer blends were capable of completing a minimum of four consecutive production cycles, wherein the PA17CS blend (PA:CS = 1:7) outperformed with respect to the working effectiveness (average cell detachment ratio= 88%) and the cell viability. Compared to the trypsin-based method, ASCs harvested from PA17CS exhibited superior stemness characteristics along with SDF-1-mediated CXCR4 chemotactic response for stem cell homing. Moreover, injection of ASCs generated from PA17CS blend could more effectively induce neovascularization and protect skin ﬂaps during an ischemic injury in a rat model.